Commercialisation of the sweetpotato value chain: Impacts on women producers in Mozambique. (September 2022) - Mayanja, Sarah; Mudege, Netsayi; Snyder, Katherine A; Kwikiriza, Norman; Munda, Eliah; Achora, Janet; Grant, Fredrick
Traditionally, sweetpotato is a woman's crop grown primarily for food in Mozambique. With the introduction of Vitamin A rich varieties, efforts were made to commercialize the crop. This study assessed the effects of this commercialization on women producers. Findings indicate that though women devoted more land to sweetpotato, men got higher yields, sold more and obtained better prices. Nonetheless, women dominated the roots value chain and increased their participation in markets. The more lucrative sweetpotato vine chain was dominated by men (75% men), as the resources and skills required to engage in this activity were a significant challenge for women. Women perceived that sweetpotato commercialization increased their ability to make production decisions, though it has not resulted in any changes in ownership of resources. Women and men both noted a subtle change in norms. Men for example perceived that their ability to make decisions had reduced, while women noted that they had taken on more leadership positions locally. These changes might be attributed to the role played by project implementors who encouraged men to allow their spouses to engage more in commercial activities. Whilst women faced challenges related to literacy, market entry and access to resources, they valued the experience obtained in improving their entrepreneurial skills. Future commercialization initiatives should work on linking women to business services and building stronger farmer-processer linkages. Efforts to sensitize men about the benefits of women's engagement in business showed some impact and should be included in further work on crop commercialization.